Overtraining and recovery. A conceptual model - Kentta, G.; Hassmen, P. (Sports Medicine, 1998)
Fiercer competition between athletes and a wider knowledge of optimal training regimens dramatically influence current training methods. A single training bout per day was previously considered sufficient, whereas today athletes regularly train twice a day or more. Consequently, the number of athletes who are overtraining and have insufficient rest is increasing. Positive overtraining can be regarded as a natural process when the end result is adaptation and improved performance: the supercompensation principle--which includes the breakdown process (training) followed by the recovery process (rest)--is well known in sports. However, negative overtraining, causing maladaptation and other negative consequences such as staleness, can occur. Physiological, psychological, biochemical and immunological symptoms must be considered, both independently and together, to fully understand the 'staleness' syndrome. However, psychological testing may reveal early-warning signs more readily than the various physiological or immunological markers. The time frame of training and recovery is also important since the consequences of negative overtraining comprise an overtraining-response continuum from short to long term effects. An athlete failing to recover within 72 hours has presumably negatively overtrained and is in an overreached state. For an elite athlete to refrain from training for > 72 hours is extremely undesirable, highlighting the importance of a carefully monitored recovery process. There are many methods used to measure the training process but few with which to match the recovery process against it. One such framework for this is referred to as the total quality recovery (TQR) process. By using a TQR scale, structured around the scale developed for ratings of perceived exertion (RPE), the recovery process can be monitored and matched against the breakdown (training) process (TQR versus RPE). The TQR scale emphasises both the athlete's perception of recovery and the importance of active measures to improve the recovery process. Furthermore, directing attention to psychophysiological cues serves the same purpose as in RPE, i.e. increasing self-awareness. This article reviews and conceptualises the whole overtraining process. In doing so, it (i) aims to differentiate between the types of stress affecting an athlete's performance: (ii) identifies factors influencing an athlete's ability to adapt to physical training: (iii) structures the recovery process. The TQR method to facilitate monitoring of the recovery process is then suggested and a conceptual model that incorporates all of the important parameters for performance gain (adaptation) and loss (maladaptation).